2022
DOI: 10.1111/eci.13927
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiome dysbiosis is recovered by restoring a normal diet in hypercholesterolemic pigs

Abstract: Background Gut microbiota is thought to modulate cardiovascular risk. However, the effect of cardiovascular primary prevention strategies on gut microbiota remains largely unknown. This study investigates the impact of diet and rosuvastatin interventions on gut microbiota composition in hypercholesterolemic pigs and associated potential changes in host metabolic pathways. Methods Diet‐induced hypercholesterolemic pigs (n = 32) were randomly distributed to receive one of the following 30‐day interventions: (I) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
(116 reference statements)
0
1
0
Order By: Relevance
“… 112 113 114 The metaorganismal TMAO-pathway was demonstrated to promote arterial thrombus growth via multiple pathways, including the induction of platelet hyperreactivity and vascular endothelial TF expression. 106 115 Of note, in a translational pig model it was recently demonstrated that the reduction of dietary fat for a time period of 30 days, resulting in reduced plasma cholesterol levels, was able to revert dysbiosis of the fecal microbiome and to reduce plasma TMAO levels, 116 a predictive functional marker for adverse cardiac events. 117 Vascular innate immune signaling, triggered by microbial-associated molecular patterns derived from the intestinal microbiota, for instance by the activation of endothelial Toll-like receptor-2 signaling in the liver resulting in enhanced vWF synthesis, is an additional mechanism linking the gut microbiota with enhanced arterial thrombus growth.…”
Section: Theme 2: Novel Mechanisms Of Thrombosismentioning
confidence: 99%
“… 112 113 114 The metaorganismal TMAO-pathway was demonstrated to promote arterial thrombus growth via multiple pathways, including the induction of platelet hyperreactivity and vascular endothelial TF expression. 106 115 Of note, in a translational pig model it was recently demonstrated that the reduction of dietary fat for a time period of 30 days, resulting in reduced plasma cholesterol levels, was able to revert dysbiosis of the fecal microbiome and to reduce plasma TMAO levels, 116 a predictive functional marker for adverse cardiac events. 117 Vascular innate immune signaling, triggered by microbial-associated molecular patterns derived from the intestinal microbiota, for instance by the activation of endothelial Toll-like receptor-2 signaling in the liver resulting in enhanced vWF synthesis, is an additional mechanism linking the gut microbiota with enhanced arterial thrombus growth.…”
Section: Theme 2: Novel Mechanisms Of Thrombosismentioning
confidence: 99%